Colonial Revenue Extraction and Modern Day Government Quality in the British Empire. (February 2017) - Broms, Rasmus
Highlights: Colonial revenue level is linked to modern day government quality in British colonies. The association is stronger when neo-European colonies are excluded. These findings call the extractive institutions hypothesis into question. Summary: The relationship between the extent of government revenue a government collects, primarily in the form of taxation, and its overall quality has increasingly been identified as a key factor for successful state building, good institutions, and—by extension—general development. Initially deriving from historical research on Western Europe, this process is expected to unfold slowly over time. This study tests the claim that more extensive revenue collection has long-lasting and positive consequences for government quality in a developmental setting. Using fiscal records from British colonies, results from cross-colony/country regression analyses reveal that higher colonial income-adjusted revenue levels during the early twentieth century can be linked to higher government quality today. This relationship is substantial and robust to several specifications of both colonial revenue and modern day government quality, and remains significant under control for a range of rivaling explanations. The results support the notion that the current institutional success of former colonies can be traced back to the extent of historical revenue extraction.